1985
DOI: 10.1128/aac.28.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of aztreonam in the treatment of severe bacterial infections

Abstract: Aztreonam (AZT) is a member of a new class of monocyclic synthetic P-lactam agents with in vitro activity against the vast majority of gram-negative bacteria, including members of the family Enterobacteriaceae and most isolates of Pseudomonas aeruginosa. The compound is inactive against aerobic, gram-positive and anaerobic bacteria. It is likely that this selective spectrum of action causes minimal disturbance of normal human fecal flora, thus decreasing the risk of overgrowth of enterococci and other resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…The percentage of superinfections (8,20,23) we found during and at the end of aztreonam treatment was also similar to that reported in comparable clinical trials in adults. Superinfections, mostly by gram-positive bacteria, were almost exclusively restricted to immunocompromised patients or to those with predisposing conditions (8,23).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The percentage of superinfections (8,20,23) we found during and at the end of aztreonam treatment was also similar to that reported in comparable clinical trials in adults. Superinfections, mostly by gram-positive bacteria, were almost exclusively restricted to immunocompromised patients or to those with predisposing conditions (8,23).…”
Section: Discussionsupporting
confidence: 74%
“…Aztreonam was well tolerated. Hematologic and biochemical side effects in our patients were similar to those described in adult patients treated with the drug (8,20,23) and in pediatric patients treated with other new beta-lactam antibiotics (1,4,12,21,22). Thus, it seems reasonably safe to use aztreonam also in severely ill patients and in patients with renal failure.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…We show here that pleurocidin notably exhibits both anticandidal and antibacterial activity against clinical isolates, which may decrease the chance of candidal superinfections normally associated with antibacterial treatment of conditions such as urinary tract infections, bacterial meningitis, and bacterial vaginosis (15,29,30). Pleurocidin may prove beneficial in the treatment or prevention of sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…The use of antimicrobial agents lacking enterococcal activity has been implicated as an important factor in the development of enterococcal superinfection (16,46,74,98,137,176,207,230). Moellering reviewed 2,107 patients treated with moxalactam and found that 2.1% developed an enterococcal superinfection during or shortly after moxalactam therapy (137).…”
Section: Nosocomial Infections and Superinfectionsmentioning
confidence: 99%